2019
DOI: 10.17533/udea.iee.v37n2e08
|View full text |Cite
|
Sign up to set email alerts
|

Profile of the nursing diagnoses in stable heart disease patients

Abstract: Objective. To identify the nursing diagnoses through reports in the medical records of patients monitored in a specialized ischemic heart disease outpatient clinic.Methods. Cross-sectional study with retrospective data collection in the medical records. From the data collected, the nursing diagnoses were proposed by the researchers and submitted for validation by specialist cardiology nurses.Results. A total of 13 nursing diagnoses were evaluated from the medical records of 50 outpatients with the following va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Corroborating the findings of other studies, participating patients showed hypertension, diabetes mellitus, dyslipidemia, and other cardiovascular diseases. We also found that smoking and obesity are associated risk factors (13)(14)(15)(16). Due to the absence of studies that analyzed the elements of the two Nds studied in the population chosen for this study, we made comparisons with studies that performed an analysis in patients with…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Corroborating the findings of other studies, participating patients showed hypertension, diabetes mellitus, dyslipidemia, and other cardiovascular diseases. We also found that smoking and obesity are associated risk factors (13)(14)(15)(16). Due to the absence of studies that analyzed the elements of the two Nds studied in the population chosen for this study, we made comparisons with studies that performed an analysis in patients with…”
Section: Discussionmentioning
confidence: 70%
“…Research with stable heart disease patients identified 13 Nds, where lifestyle (00168) and activity intolerance (00092) stand out. However, rdcTP (00200) and rAi (00094) presented less agreement between specialist nurses (15), which shows the difference between Nds of the acute, subacute and chronic faces. The evidence of activity intolerance (00092) shows that the presence of dyspnea on exertion, fatigue, the imbalance between oxygen supply and demand, stress discomfort, and the presence of angina is a common feature (15).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The nursing diagnosis of risk-prone health behavior has been previously identified in Brazilians who have stable heart disease, Turkish agricultural laborers, Brazilian and Dutch school adolescents, and people with mental disorders (Brusamarello et al, 2013;Busch et al, 2013;Cardoso et al, 2019;Karatas et al, 2018;Leal et al, 2016). Thus, riskprone health behavior has been studied among various categories of vulnerable individuals.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary, for this, in addition to raising awareness of their self-care, that the client feels welcomed and understood in all its aspects, in an integral way, with the nursing consultation being a moment of welcome, listening and guidance, transcending the care and providing transformations in individuals in terms of unhealthy living habits. [9][10] Nursing consultation is considered a tool used in this search for continuity of care and effective communication, that is, patient-centered care. 11 It is known that, for nurses to exercise their practice in an educational, administrative, research or assistance way, a solid foundation is needed, which guarantees quality, safe and riskfree care.…”
mentioning
confidence: 99%